Determining The Relationship Between Exercise Dependence And Narcissism Levels Of Athletes: Life Sciences-Psychology for curing mental health - Abdullah Altunhan; Ünsal Tazegül (International Journal of Life Science and Pharma Research, 2022)
There exist a positive relationship between exercise and narcissistic personality. Athletes who develop narcissistic personality traits wanted to be trained continuously to be successful. As a result, they become addicted to exercise. Athletes with narcissistic personalities should seek help from experts so that they do not become addicted to exercise. Narcissistic people tend to be addicted to exercise. Narcissistic athletes should be constantly checked by their trainers to prevent them from becoming exercise addicts.There are currently limited investigations that have examined the relationship between narcissistic personality traits and exercise dependence. The purpose of the present study was to explore the relationship between exercise dependence levels and narcissistic personalities of male athletes in wrestling, weight lifting, and body building. In this study, narcissistic personality inventory and exercise dependence scale were used as a data collection tool. Statistical software (SPSS 20 version) was used to analyze the data. It was observed that the data is normally distributed and homogeneous. Descriptive statistical analysis and Spearman correlation analysis were used to determine the direction and severity of the relationship between the variables. The study group consisted of 25 wrestlers, 23 weight-lifters, and 14 bodybuilders who achieved the first 3 ranks in Turkey Championships. As a result of descriptive statistical analysis, dropping exercise scores of athletes were as 3.866, sustainability scores were as 2.806, tolerance scores were as 4.634, lack of control scores was as 1.634, decrease in other activities scores was as 1.581, duration scores were as 4,796, intention effect scores were as 2.753, total exercise addiction scores were as 3.153 and narcissism scores were determined as 8,048. At the end of the study, it was determined that the athletes under the sample had a relationship between narcissism and exercise addiction levels. According to descriptive statistical analysis, wrestlers were observed to get the highest scores in lack of control, sustainability, dropping exercise sub-dimensions.